Effects of the plant extract silymarin on prolactin concentrations, mammary gland development, and oxidative stress in gestating gilts. Issue 7 (1st July 2014) - Farmer, C.; Lapointe, J.; Palin, M.-F.
Abstract: The impacts of supplementing the diet of gestating gilts twice daily with 4 g of the plant extract silymarin on circulating hormonal concentrations, oxidative status, mammary development, and mammary gene expression at the end of gestation were determined. Gilts were fed conventional diets during gestation and on d 90 they were assigned as controls (CTL; n = 16) or treated (TRT; n = 17) animals. Treatment consisted of providing 4 g of silymarin twice daily until d 110, at which time all gilts were slaughtered to collect mammary tissue for compositional analyses and measures of gene expression and oxidative status, and liver and corpora lutea for measures of oxidative stress variables. Blood samples for hormonal assays and evaluation of oxidative stress biomarkers were obtained on d 89, 94, and 109 of gestation. Silymarin increased ( P = 0.05) circulating concentrations of prolactin over all samples in the repeated in time analysis. In separate analyses for each sampling time, prolactin concentrations in TRT gilts tended ( P < 0.10) to be greater than in CTL gilts on d 94 of gestation. Repeated in time analysis also revealed that silymarin reduced ( P ≤ 0.05) plasmatic accumulation of biomarkers of oxidative damage to protein (protein carbonyls) between d 89 and 109. There was no effect ( P > 0.10) of treatment on progesterone, estradiol, leptin, or 8-hydroxy-2'-deoxyguanosine concentrations. Percent fat in mammary parenchyma was greater ( P ≤ 0.05), percent protein was lesser ( P ≤ 0.05), and concentrations of both RNA ( P ≤ 0.01) and DNA ( P < 0.05) were lesser in TRT than CTL gilts. Mammary parenchyma from TRT gilts had lower ( P ≤ 0.05) mRNA abundance for STAT5A and leptin and tended to have lower ( P ≤ 0.10) abundance for STAT5B than CTL gilts. Silymarin reduced ( P ≤ 0.001) protein carbonyls concentrations in liver of TRT gilts. No effect of treatment was observed on antioxidant gene expression and enzymatic activities in liver samples while total superoxide dismutase activity tended to be higher ( P ≤ 0.10) in the corpora lutea of TRT animals when compared with CTL. This is the first demonstration that, in female pigs, silymarin can increase prolactin concentrations and protect against oxidative stress, yet the increase in prolactin was not enough to have beneficial effects on mammary gland development in late gestation.